Development of character assessment instrument on English learning for middle school students - Andi Abdurrahman Manggaberani; Nur Hidayanto Pancoro Setyo Putro (Universitas Muhammadiyah Malang, 2024)
There is a present-day necessity to construct character education assessment instruments in English courses. Employing the ADDIE development model, this research undergoes stages encompassing analysis, design, development, implementation, and evaluation to craft a meticulously designed assessment instrument. The resulting instrument is a self-assessment for English subjects, subjected to scrutiny through both Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). The instrument attests to content validity, indicated by an Aiken index of 0.955, and construct validity using EFA & CFA. Outcomes showcasing loading factor values exceeding 0.4 for each item and the model for measuring student character aligns seamlessly with the hypothesized model, substantiated by statistical results of p-values = 0.056; CFI = 0.979; TLI = 0.972; RMSEA = 0.031; SRMR = 0.055. Furthermore, the item reliability in each dimension/factor surpasses 0.7. The study's revelations uncover that 46% of students predominantly concentrate on character development, while 35% prioritize character emphasis. Cultivated character for 14%, whereas a mere 5% of students necessitate guidance. This instrument not only guides educators and researchers in developing character assessment tools but also meets valid and reliable criteria, ensuring credibility and usability across various education levels.